MENGGAGAS PENGEMBANGAN AKUNTANSI SYARI’AH PENDEKATAN INTEGRATIF-INTERKONEKTIF - Musthofa, Ujang Hanief (ASAS, 2011)
Abstak: There has been dichotomy in the Muslim world between secular and religious science. Hence, a Muslim is ‘forced’ to choose between the two. In Indonesian case, this can be seen in the distinction of educational institutions: madrasah and school. Another fact is that Muslims experienced severe colonialist occupation which brought secular sciences. As a result, this strengthens the stigmatization among particular Muslims towards those sciences. As world economy has been under strong influence of capitalism, Muslims try to develop their own economic system. As to secular science, Muslims make great effort to build their own science. Through ‘Islamization’ of secular sciences, Muslims attempt to found Islamic science. Among the sciences is accounting, which is expected to be deconstructed and metamorphose into Islamic (Shari’ah) Accounting. By using integrative-interconnective approach, Shari’ah Accounting is supposed to reflect integrative Islamic values in the whole of its aspects. Keywords: Secular science, Islamization, integrative-interconnective approach, Shari’ah Accounting.